2015
DOI: 10.1016/j.ebiom.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Can Identify Pulmonary Tuberculosis in HIV-infected Drug Users Months Prior to Clinical Diagnosis

Abstract: BackgroundCurrent diagnostic tests cannot identify which infected individuals are at risk for progression to tuberculosis (TB). Our aim was to identify biomarkers which can predict the development of TB prior to clinical diagnosis.MethodIn a retrospective case–control study, RNA of 14 HIV-infected drug users obtained before TB diagnosis (cases) and of 15 who did not develop TB (controls) was analyzed for the expression of 141 genes by dcRT-MLPA followed by Lasso regression analysis.FindingsA combined analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…The dcRT-MLPA method has been applied in different studies assessing TB biomarkers for different purposes 15 16 21 22 23 24 25 , but few studies have been conducted in children 17 . A recent publication, which provides a proof-of-concept for the use of this assay in a large cohort of adults across four different African populations, identified increased FCGR1A expression as the single most consitent classifier of TB disease compared to latent TB infection (LTBI) irrespective of HIV-infection 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The dcRT-MLPA method has been applied in different studies assessing TB biomarkers for different purposes 15 16 21 22 23 24 25 , but few studies have been conducted in children 17 . A recent publication, which provides a proof-of-concept for the use of this assay in a large cohort of adults across four different African populations, identified increased FCGR1A expression as the single most consitent classifier of TB disease compared to latent TB infection (LTBI) irrespective of HIV-infection 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The first study to report an association between gene expression in peripheral blood cells and risk of TB disease compared 15 HIV-infected drug users who ultimately progressed to active TB with 16 who remained disease free. Expression of two transcripts, IL-13 and AIRE, was found to correlate with risk of TB (207).…”
Section: Biomarkers In Human Tbmentioning
confidence: 96%
“…In a smaller study, we previously reported a simple CoR that predicted onset of TB disease months before clinical manifestation of disease in HIV-infected intravenous drug users from the longitudinal Amsterdam cohort study. Targeted host blood gene expression profiling by dual colour reverse transcriptase multiplex ligand probe amplification 90 found that elevated expression of IL-13 in the absence of AIRE discriminated those who would develop future TB from those who remained TB-free for at least 2 years. Interestingly, individuals carrying the IL-13/AIRE CoR had increased expression of type I IFN-related genes, agreeing with the African CoR signature discussed above.…”
Section: Predictive Correlates Of Tb Riskmentioning
confidence: 99%